Properties of cellulose nanofibre networks prepared from nevEr-dried and dried paper mill sludge - Adu, Cynthia; Jolly, Mark R.; Oksman, Kristiina; Zhu, Chenchen; Berglund, Linn; Eichhorn, Stephen J. (Cranfield University, 2018)
The data enclosed is the data used in the paper "Properties of cellulose nanofibre networks prepared from never-dried and dried paper mill sludge". The raw data from tensile tests of cellulose nanofibres prepared from paper mill sludge is attached including the x-ray diffraction pattern of the material
Keywords: 'cellulose'; 'Paper Mill Sludge'; 'dried'; 'nanocellulose materials'; 'waste streams'; 'Biomaterials'; 'Timber; Pulp and Paper'